GROUP DEVELOPMENT PLAY IN THE DANCE MOVEMENT - DN, Rr. Ruth Hertami; Adlin, Dilinar; Panggabean, Deo Demonta (Universitas Negeri Medan, 2018)
AbstractThe movement that had been carried out in Early Childhood Education (PAUD) in the Cahaya and Manca playgroups in Delitua village was only on gymnastics or sports. The most basic cause is the absence of competent teachers in the field of dance movement. In addition, the available teachers do not understand optimally about how to provide dance material that is right at the age of the children in the playgroup. Based on this situation, the proposed team through the Coaching of Playgroups in Dance Motion, fostering and strengthening dance activities for children Light playgroups, as well as four teachers in the Manca playgroup. The method applied is guidance and stabilization of mastery of dance movements for the age of children, namely: (1) Butterfly dance which includes hand, foot, head, shoulder and hip movements, and (2) Flower Party dance which includes motion hands, feet, head, shoulders, and hips. Through this guidance and consolidation, 2 (two) new dances appeared, which were appropriate for the age of the children and packaged in audiovisual media, so that they could be used as learning media in the two playgroups.Keywords: Playgroup, Butterfly dance, Flower Party dance.